Groundwater Resource Characterisation and Management Aspects - Gomo, Modreck (IntechOpen, 2019)
This book covers aspects of groundwater resource characterisation and management. The inherent heterogeneous and isotropic nature of aquifers coupled with the unpredictable effects of climate change calls for continuous improvement and understanding of hydrogeology site characterisation techniques in theory and application to better understand and manage groundwater. We believe that this book will be useful for various professionals involved in groundwater-related work to improve the theoretical and practical understanding of hydrogeology site characterisation techniques and groundwater resource management skills.